Tailoring Process and Impact Evaluation of a "Cash-Plus" Program: The Value of Using a Participatory Program Impact Pathway Analysis. Issue 7 (28th May 2020) - Savy, Mathilde; Briaux, Justine; Seye, Moustapha; Douti, Mireille P; Perrotin, Gautier; Martin-Prevel, Yves
ABSTRACT: Background: Evaluations are often limited to affirming what impact health and nutrition interventions have, without providing enough insights into "how/why" impacts are achieved. Objectives: This article describes how a Program Impact Pathway (PIP) analysis was used to tailor theory-driven impact and process evaluation of a "Cash-Plus" program combining unconditional cash transfers with behavior change communication (BCC) activities, which was implemented to improve children's growth in Togo. Methods: A theoretical PIP diagram was developed using existing literature, program documentation, and interviews with the program's stakeholders at the central level. Next, the PIP diagram was refined through 2 regional participatory workshops, 6 mo after the program began. Workshop participants were multilevel field implementers and were asked to 1 ) discuss their vision of the program's objectives; 2 ) describe the "inputs–process–outputs–outcomes–impacts" flow; 3 ) reflect on modifiers that may arise along the PIP; and 4 ) report bottlenecks in the program's conception or implementation and suggest corrective actions. The PIP was used to determine research questions that should be investigated during impact or process evaluation and guided the choice of data collection methods and tools. Results: The PIP analysis identified 3 impact pathways, all based on the synergy between cash and raised women's knowledge. Along these pathways, the motivation and workload of frontline workers, along with issues in cash flow, were identified as factors that may affect the delivery of activities, whereas women's control over resources, time availability, support from relatives, and the presence of markets and health and school services were recognized as factors that may influence the uptake of activities. Improved communication between stakeholders and increased involvement of husbands were suggested for better impact achievement. Conclusions: The participatory PIP analysis helped implementers and evaluators to share a common vision of the program's objective and logic, encouraged communication across sectors, and facilitated course-adjustments of the program. Abstract : This article showcases how a Program Impact Pathway analysis can be operationalized to conduct comprehensive process and impact evaluations of cash transfer programs.